2006
DOI: 10.1002/cne.21041
|View full text |Cite
|
Sign up to set email alerts
|

Axotomy induces contrasting changes in calcium and calcium-binding proteins in oculomotor and hypoglossal nuclei of Balb/c mice

Abstract: Motor neurons with different susceptibility to degeneration have been identified in amyotrophic lateral sclerosis (ALS). Increase of intracellular calcium has been proposed as a mediator, amplifying the damage through a positive feedback of the known pathological processes. Accordingly, the potential of motor neurons to limit calcium increases during injury might be proportional to their viability. A basic mechanism of reducing calcium amplitudes depends on the calcium-buffering capacity, determined by the cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 87 publications
1
25
0
Order By: Relevance
“…On the basis of in vitro physiology measurements in oculomotor and hypoglossal neurons, the prototypes of motor neurons with high and low CaBP content, respectively, a correlation was proposed between the CaBP content and the ability of the motor neurons to resist calcium-mediated injury (Lips and Keller, 1998;Vanselow and Keller, 2000). Our earlier electron microscopic study following axotomy/target deprivation in these same motor nuclei in vivo provided further support for this concept: a lower increase in calcium level and less significant degeneration were demonstrated in the oculomotor neurons in which the PV content was higher than that in the hypoglossal motor neurons, in which PV and CB could not be detected (Obál et al, 2006).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…On the basis of in vitro physiology measurements in oculomotor and hypoglossal neurons, the prototypes of motor neurons with high and low CaBP content, respectively, a correlation was proposed between the CaBP content and the ability of the motor neurons to resist calcium-mediated injury (Lips and Keller, 1998;Vanselow and Keller, 2000). Our earlier electron microscopic study following axotomy/target deprivation in these same motor nuclei in vivo provided further support for this concept: a lower increase in calcium level and less significant degeneration were demonstrated in the oculomotor neurons in which the PV content was higher than that in the hypoglossal motor neurons, in which PV and CB could not be detected (Obál et al, 2006).…”
mentioning
confidence: 82%
“…In order to test the hypothesis of the protective role of CaBPs more directly, the same population of motor neurons, but with different CaBP contents should be challenged experimentally. For this purpose, a transgenic homozygous mouse strain with elevated PV content (PVþ/þ) has been developed (Beers et al, 2001) and applied in axotomy/target deprivation experiments, similarly as in our earlier study (Obál et al, 2006). The changes in level of the intracellular calcium in the hypoglossal motor neurons were determined in the 21-day period after the lesion, and compared with the corresponding data obtained in wild-type animals.…”
mentioning
confidence: 99%
“…The extra-ocular muscle remains largely innervated even in the terminal stages of the disease (Tjust et al, 2012), and a recent study using end-stage ALS patient material found significant decreases in synaptic protein levels at the NMJs of limb muscles compared to extra-ocular muscles that could explain this phenomenon (Liu et al, 2014). In addition, motor neurons that are resistant to degeneration express higher levels of calcium buffering proteins which may allow them to be more resistant against excitotoxic stimuli and may explain the resistance of the oculomotor and Onuf's nucleus to degeneration in ALS (Obál et al, 2006). Interestingly, pharmacological modulation of calcium at the NMJ using calpain inhibitors has been shown to protect the distal cytoskeleton from degradation in cases of autoimmune peripheral neuropathies (O'Hanlon et al, 2003), and support the idea of protecting the distal cytoskeleton as a therapeutic approach for preventing or delaying distal axonopathies (see below for more discussion on the role of the axonal cytoskeleton and ALS pathogenesis).…”
Section: Theories On the Cause(s) Of Salsmentioning
confidence: 99%
“…This is further supported by other studies in adult rats where significant functional recovery occurred in treated rats (2,3-dihydro-6-nitro-7-sulfamoyl-benzo(f)quinoxaline [NBQX] or basic fibroblast growth factor [BFGF]) in the absence of any significant differences in white matter sparing compared to untreated controls (Rabchevsky et al, 2000;Wrathall et al, 1997). Previous experimental studies have demonstrated a reduction in NeuN-IR following brain injury and SCI (Manley et al, 2006;Xu et al, 2006), and this seems to involve a rapid dephosphorylation event (Lind et al, 2005;Obal et al, 2006); however, the mechanism behind this reduction is unclear. Reduction of NeuN-IR does not necessarily lead to cell death (Unal-Cevik et al, 2004); therefore, we cannot be certain that the reduction in NeuN immunoreactivity observed in the current study is indicative of the extent of gray matter damage or sparing at the lesion site.…”
Section: Comparison Of Adult and Neonatal Datamentioning
confidence: 97%